(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Women’s empowerment characterized as improving the capacity of women to get to the constituents of development specifically health, education, earning opportunities, rights and political participations. Women empowerment in India is subject to various variables like education status, economic wellbeing, land status and age. This paper is engaged to economic participations and opportunities for women. There is close connection between economic development and women’s empowerment.This paper means to break down the effect of Economic Development on the status of women in India and attempts to consider how chronicled observations, prejudices, predispositions and convictions with respect to women in the public eye have prompted propagation of „deprivation and discrimination‟ against the women and in result weakening the general status of women even in today’s world. For any economy, growth identifies with an expansion in per capita salary which reflects just quantitative perspective in dismissal of distributive equity in that economy. Economic development, then again, is a more extensive idea relating not exclusively to the quantitative angle yet in addition subjective part of conveyance of salary and pay disparity in regard of its dispersion among the populace and furthermore other socio-economic factors too, subsequently it is additionally alluded as a multi-dimensional idea incorporating increment in per capita pay as well as progress in expectations for everyday comforts, educational achievement of individuals, mitigation of neediness, health conditions and dietary status, status of women and their empowerment and so on.